Use of Augmented Reality in Reconstructive Microsurgery: A Systematic Review and Development of the Augmented Reality Microsurgery Score - Al Omran, Yasser; Abdall-Razak, Ali; Sohrabi, Catrin; Borg, Tiffanie-Marie; Nadama, Hayat; Ghassemi, Nader; Oo, Khine; Ghanem, Ali M. (Journal of Reconstructive Microsurgery, 2020)
Background Augmented reality (AR) uses a set of technologies that overlays digital information into the real world, giving the user access to both digital and real-world environments in congruity. AR may be specifically fruitful in reconstructive microsurgery due to the dynamic nature of surgeries performed and the small structures encountered in these operations. The aim of this study was to conduct a high-quality preferred reporting items for systematic reviews and meta-analyses (PRISMA) and assessment of multiple systematic reviews 2 (AMSTAR 2) compliant systematic review evaluating the use of AR in reconstructive microsurgery.Methods A systematic literature search of Medline, EMBASE, and Web of Science databases was performed using appropriate search terms to identify all applications of AR in reconstructive microsurgery from inception to December 2018. Articles that did not meet the objectives of the study were excluded. A qualitative synthesis was performed of those articles that met the inclusion criteria.Results A total of 686 articles were identified from title and abstract review. Five studies met the inclusion criteria. Three of the studies used head-mounted displays, one study used a display monitor, and one study demonstrated AR using spatial navigation technology. The augmented reality microsurgery score was developed and applied to each of the AR technologies and scores ranged from 8 to 12.Conclusion Although higher quality studies reviewing the use of AR in reconstructive microsurgery is needed, the feasibility of AR in reconstructive microsurgery has been demonstrated across different subspecialties of plastic surgery. AR applications, that are reproducible, user-friendly, and have clear benefit to the surgeon and patient, have the greatest potential utility. Further research is required to validate its use and overcome the barriers to its implementation.
Keywords: augmented reality; reconstruction; technology